The sustainable cycle between lean production and auditing practices and its efficiency in improving supplier relationships and green supply chains - Huang, Xiang; Chen, Ping-Kuo; Zhang, Guodao (Journal of Business Economics and Management, 2023)
This study explores why a sustainable cycle is induced when manufacturers implement auditing in combination with lean production. Furthermore, it verifies whether this sustainable cycle enhances process integration and risk resilience, thereby allowing the manufacturer to build strong cooperation with suppliers, which further produces a positive effect on the green supply chain. Sociotechnical systems theory is our theoretical basis, and calculating Spearman’s rank correlation coefficient and estimating PLS regressions are the main methods used. The results show that the implementation of auditing induces two driving forces: internal responsibility and the ability to respond to emergencies. These two forces drive suppliers to actively and positively cooperate with lean practices to ensure that the effect of those practices is strengthened. Moreover, stronger lean practices also produce two feedback forces – expanded tolerance for auditing and expanded acceptance of auditing interventions – that strengthen auditing practices. As a result, the mutually continuous strengthening of lean production and auditing practices is produced, which further becomes a sustainable cycle. This cycle can continue to enhance process integration and increase risk resilience, build strong cooperation with suppliers, and improve the green supply chain.